PENGARUH KEPEMIMPINAN DAN KOMPETENSI PEGAWAI TERHADAP KUALITAS PELAYANAN PENDAFTARAN TANAH PERTAMA KALI DI KANTOR PERTANAHAN KOTA BANDUNG - Lucky Sugiharti; Aep Saepudin; Rezky Afiahtul Barokah (Journal Publicuho, 2023)
In public service organizations, service quality is a very important factor to pay attention to in order to gain public trust. This study aims to determine the effect of leadership and employee competence on service quality. The sample in this study is all employees as many as 70 people. Data analysis in this study used multiple linear regression analysis using the SPSS 23 application for windows. The results of this study indicate that employee leadership and competence have a positive and significant influence on the quality of land registration services in the city of Bandung. The result of the coefficient of determination is also obtained at 64.3%, this result indicates that leadership and employee competence have a fairly strong influence. This research also has implications for institutions, especially for leaders to pay more attention to employees and protect them so that service quality can be improved properly.